The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1159/000437207
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Combined with Immature Dendritic Cells Attenuates Obliterative Bronchiolitis in Trachea Allograft Rats by Regulating the Balance of Regulatory and Effector T Cells

Abstract: Background: Obliterative bronchiolitis (OB) ranks as the major obstacle for long-term survival of lung transplantation patients. Rapamycin (Rapa) has recently been confirmed as an immunosuppressant for antirejection due to its suppressive role in T cell activation. Here, we explore the effect of Rapa combined with immature dendritic cells (imDCs) on OB in trachea allograft rats. Methods: The effect of bone marrow-derived imDCs or Rapa-imDCs on lymphocyte cells and CD4+ T cells were evaluated by meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
(48 reference statements)
3
9
0
Order By: Relevance
“…In our preliminary study in which transplantation was performed between Brown Norway and LEW rats, the infusion of BMSCs promoted graft rejection, and it was also reported by other researchers that BMSCs promoted rejection between ACI and LEW rats (Inoue et al, ),—as such, we used the combination of WIS and LEW rats for the transplantation model. Some authors used this combination to investigate the in vivo transplantation model, and also in our study the untreated control group showed acute graft rejection with this combination (Dong, Wang, Liu, Zhao, Chen, Li, & Li, ). Third, we did not analyze the other immunological effects of recipient BMSCs, such as their homing effects, the induction of T cell regulation, and the modulation of dendritic cell maturation.…”
Section: Discussionsupporting
confidence: 55%
“…In our preliminary study in which transplantation was performed between Brown Norway and LEW rats, the infusion of BMSCs promoted graft rejection, and it was also reported by other researchers that BMSCs promoted rejection between ACI and LEW rats (Inoue et al, ),—as such, we used the combination of WIS and LEW rats for the transplantation model. Some authors used this combination to investigate the in vivo transplantation model, and also in our study the untreated control group showed acute graft rejection with this combination (Dong, Wang, Liu, Zhao, Chen, Li, & Li, ). Third, we did not analyze the other immunological effects of recipient BMSCs, such as their homing effects, the induction of T cell regulation, and the modulation of dendritic cell maturation.…”
Section: Discussionsupporting
confidence: 55%
“…This either points to special features of the sensitizing allergens, which become imprinted onto the involved dendritic cells, as discussed and entertained by the authors, or rather mirrors already elevated allergen-specific T effector cell levels present in such specifically sensitized individuals. These findings, together with the observation of Dong et al [57] that rapamycin-treated immature dendritic cells lead to the induction of Treg cells, add additional support to the concept that dendritic cells critically shape the T cellular immune response. Antigen-presenting cells receive important cues, such as ‘danger signals', by specifically sensing their environment with their specific set of surface receptors, including histamine receptors [58].…”
Section: Monocytes and Dendritic Cellssupporting
confidence: 63%
“…Previous studies have shown that rapamycin, a typical mTOR inhibitor, inhibits T cell proliferation by preventing them from entering proliferative cell cycle . It has been generally accepted that rapamycin promotes CD4 + Foxp3 + T reg development . Here we demonstrated that kaempferol suppressed the proliferation of T cells and also dampened their mTOR signaling.…”
Section: Discussionsupporting
confidence: 49%